Liberdade em Jean-Jacques Rousseau - Rossetto, Maicon Rodrigo (2009)
The present dissertation takes as object of its central study the liberty theme based on the work of the philosopher Jean-Jacques Rousseau. The dissertation tackles it from the descriptions the author undertakes from the natural liberty, that is to say, the man considered toward himself and his fellows , the man toward social ties, and considered under the perspective of an ideal society of free citizens, just as it is presented in the social contract. The dissertation demonstrates the undertaken research in three moments: the first clarifies the thesis of Rousseau according to what it says the men is born free end the liberty is distinctive from the human being, and of that the man can ever dispose, the second demonstrates the descriptions of Rousseau about the conflicts between the natural liberty and the relation into the societies that were constituted in the line of the sociability, finally, it demonstrates the reflections of Rousseau about the conventional liberty , that is to say, the way that the author solves , at least from a normative point of view, the conflict between nature and society through an contract that preserves the individual as well as the public liberty. The matter is to know the author justify the institutionalization of this liberty and the presumption is that it is ensured by law. Even though the liberty theme is in the Rousseau work as a whole, the examined main texts in this search were: Speech about the origin and the fundaments of inequality among men, Emilio and From The Social contract.